Electrolytic capacitors and capacitor components

By adjusting the electrode potential of the solid electrolyte layer in the electrolytic capacitor to make it higher than the electrode potential of the cathode lead-out layer, the problem of oxidation deterioration of conductive polymers is solved, and the reliability of the electrolytic capacitor is improved.

CN115280443BActive Publication Date: 2025-03-28PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180020473.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-25
Filing Date
2021-03-18
Publication Date
2025-03-28
Estimated Expiration
2041-03-18

AI Technical Summary

Technical Problem

The existing electrolytic capacitors with solid electrolyte layers are prone to oxidation and deterioration of conductive polymers under high temperature environments, resulting in an increase in equivalent series resistance (ESR) and a decrease in electrostatic capacitance, reducing the reliability of the electrolytic capacitor.

Method used

In the capacitor element of the electrolytic capacitor, the electrode potential Ps of the solid electrolyte layer is higher than the electrode potential P1 of the cathode lead-out layer, thereby suppressing the oxidation deterioration of the conductive polymer.

Benefits of technology

It effectively suppresses the increase of ESR and the decrease of electrostatic capacitance, and improves the reliability of the electrolytic capacitor, especially in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115280443B_ABST
    Figure CN115280443B_ABST
Patent Text Reader

Abstract

The electrolytic capacitor includes a capacitor element. The capacitor element includes: an anode body, a dielectric layer formed on the surface of the anode body, a solid electrolyte layer covering at least a portion of the dielectric layer, and a first layer in contact with the solid electrolyte layer and covering at least a portion of the solid electrolyte layer. The first layer constitutes at least a portion of the cathode lead layer. The electrode potential P of the solid electrolyte layer s Higher than the electrode potential P1 of the first layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a capacitor element including a solid electrolyte layer containing a conductive polymer and an electrolytic capacitor including the capacitor element. Background Art

[0002] As a small and large-capacitance capacitor with low ESR (equivalent series resistance), an electrolytic capacitor having a capacitor element having a solid electrolyte layer containing a conductive polymer is considered promising. The capacitor element, for example, comprises an anode body, a dielectric layer formed on at least a portion of the surface of the anode body, a solid electrolyte layer covering at least a portion of the dielectric layer, and a cathode lead layer covering at least a portion of the solid electrolyte layer. An electrolytic capacitor having a solid electrolyte layer is also called a solid electrolytic capacitor.

[0003] Patent Document 1 proposes using a conductive polymer complexed with an ionic polymer in a solid electrolytic capacitor.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2005-281410 Summary of the invention

[0007] Problems to be solved by the invention

[0008] An electrolytic capacitor according to one aspect of the present invention comprises a capacitor element, the capacitor element comprising an anode body, a dielectric layer formed on a surface of the anode body, a solid electrolyte layer covering at least a portion of the dielectric layer, and a first layer in contact with the solid electrolyte layer and covering at least a portion of the solid electrolyte layer, the first layer constituting at least a portion of a cathode lead layer, and an electrode potential P of the solid electrolyte layer s Higher than the electrode potential P1 of the first layer.

[0009] A capacitor element according to another aspect of the present invention comprises an anode body, a dielectric layer formed on a surface of the anode body, a solid electrolyte layer covering at least a portion of the dielectric layer, and a first layer in contact with the solid electrolyte layer and covering at least a portion of the solid electrolyte layer, wherein the first layer constitutes at least a portion of a cathode lead layer, and an electrode potential P of the solid electrolyte layer is s Higher than the electrode potential P1 of the first layer.

[0010] An electrolytic capacitor in which an increase in ESR is suppressed can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1It is a schematic cross-sectional view of an electrolytic capacitor according to one embodiment of the present invention. DETAILED DESCRIPTION

[0012] Before describing the embodiments, problems existing in the conventional technology are briefly described as follows.

[0013] For electrolytic capacitors with solid electrolyte layers, the conductive polymer contained in the solid electrolyte layer slowly oxidizes and degrades, and the ESR increases. If the conductive polymer oxidizes and degrades, the resistance of the solid electrolyte layer increases and the electrostatic capacitance decreases. When such an increase in ESR or a decrease in electrostatic capacitance occurs, the reliability of the electrolytic capacitor decreases. In particular, when the electrolytic capacitor is exposed to a high temperature environment for a long time, the oxidative degradation of the conductive polymer becomes significant, which is prone to an increase in ESR or a decrease in electrostatic capacitance.

[0014] Generally speaking, when the electrode potential of a metal becomes high, it is less likely to be oxidized than when the electrode potential is low. If a component containing a first metal is in contact with a component containing a second metal whose electrode potential is lower than that of the first metal, and components such as water molecules that are responsible for electron transfer are present, only the second metal is oxidized, forming a local battery.

[0015] In the case of an electrolytic capacitor, water may enter the electrolytic capacitor, which may promote oxidation degradation of the conductive polymer. It has been found that one of the main causes of this oxidation degradation is that the electrode potential of the solid electrolyte layer is lower than the electrode potential of the cathode lead layer in contact with the solid electrolyte layer, thereby promoting oxidation of the conductive polymer preferentially. Oxidative degradation of conductive polymers is particularly significant in high temperature environments.

[0016] Based on this new knowledge, in the electrolytic capacitor or capacitor element of the present invention, the electrode potential P of the solid electrolyte layer is set to s The electrode potential P1 is higher than that of the first layer which is in contact with the solid electrolyte layer, covers at least a portion of the solid electrolyte layer, and constitutes at least a portion of the cathode lead layer.

[0017] By making the electrode potential P of the solid electrolyte layer s The electrode potential P1 higher than the first layer suppresses oxidation of the conductive polymer contained in the solid electrolyte layer, and suppresses degradation of the solid electrolyte layer. As a result, the increase in ESR is suppressed. In addition, the increase in resistance accompanying degradation of the solid electrolyte layer is suppressed, thereby suppressing the decrease in electrostatic capacitance. Therefore, the reliability of the electrolytic capacitor can be improved.

[0018] The electrode potential P of the solid electrolyte layer sFor example, the conductivity can be adjusted by selecting or adjusting the type of conductive polymer, the type of dopant, the ratio of the dopant, the potential applied when the conductive polymer is formed by polymerization (hereinafter referred to as polymerization potential), and the current. When the conductive polymer is generated on a flat surface to form a solid electrolyte layer, the electrode potential P of the solid electrolyte layer is s A certain degree of correlation can be observed between the potential and the polymerization potential. However, in reality, in an electrolytic capacitor, a dielectric layer is formed along the inner wall of the holes and pits (pits) on the surface of the anode body, which is porous at least on the surface layer, and a solid electrolyte layer is also formed along the inner wall of the holes and pits in a manner covering the dielectric layer. Therefore, the electrode potential P of the solid electrolyte layer of the electrolytic capacitor is s It is not uniformly related to the polymerization potential.

[0019] It should be noted that the electrode potential P s and P1 is a silver / silver chloride electrode (Ag / Ag + ) is taken as the value measured at the reference electrode.

[0020] Hereinafter, the electrolytic capacitor and the method for manufacturing the same according to the present invention will be described in more detail with reference to the drawings as needed.

[0021] [Electrolytic capacitors]

[0022] The electrolytic capacitor includes one or more capacitor elements. s When the electrolytic capacitor includes two or more capacitor elements, it is preferred that P s > P1, preferably in more than 75% of the capacitor elements P s >P1, and preferably P s >P1.

[0023] (Capacitor Components)

[0024] (Anode)

[0025] The anode body may contain a valve metal, an alloy containing a valve metal, a compound containing a valve metal, and the like. These materials may be used alone or in combination of two or more. As the valve metal, for example, aluminum, tantalum, niobium, and titanium are preferably used. An anode body having a porous surface may be obtained, for example, by roughening the surface of a substrate (a foil-shaped or plate-shaped substrate, etc.) containing a valve metal. Roughening may be performed, for example, by etching treatment, etc. In addition, the anode body may also be a formed body of particles containing a valve metal or a sintered body thereof. It should be noted that the sintered body has a porous structure.

[0026] (Dielectric layer)

[0027] The dielectric layer is an insulating layer that functions as a dielectric and is formed in a manner that covers at least a portion of the surface of the anode body. The dielectric layer is formed by anodizing the valve action metal on the surface of the anode body by chemical conversion treatment or the like. The dielectric layer only needs to be formed in a manner that covers at least a portion of the anode body. The dielectric layer is usually formed on the surface of the anode body. Since the dielectric layer is formed on the porous surface of the anode body, it is formed along the inner wall surface of the pores and pits on the surface of the anode body.

[0028] The dielectric layer includes an oxide of a valve metal. For example, when tantalum is used as the valve metal, the dielectric layer includes Ta2O5, and when aluminum is used as the valve metal, the dielectric layer includes Al2O3. It should be noted that the dielectric layer is not limited to this, as long as it is a layer that functions as a dielectric.

[0029] (Solid electrolyte layer)

[0030] The solid electrolyte layer is formed on the surface of the anode body in a manner that sandwiches the dielectric layer and covers the dielectric layer. The solid electrolyte layer does not necessarily need to cover the entire dielectric layer (the entire surface), as long as it is formed in a manner that covers at least a portion of the dielectric layer. The solid electrolyte layer constitutes at least a portion of the cathode body of the electrolytic capacitor. The cathode body generally includes a solid electrolyte layer and a cathode lead layer.

[0031] In the electrolytic capacitor or capacitor element of the present invention, the electrode potential P of the solid electrolyte layer is s Higher than the electrode potential P1 of the first layer contained in the cathode extraction layer. s The difference from P1 is, for example, 0.02 V or more, preferably 0.05 V or more, and more preferably 0.1 V or more. s When the difference from P1 is within such a range, oxidative degradation of the solid electrolyte layer can be further suppressed.

[0032] The electrode potential P of the solid electrolyte layer s For example, it is greater than 0.2 V, and may be greater than 0.22 V, or may be greater than 0.25 V. Although it also depends on the electrode potential P1 of the first layer, by s When the content is within this range, it is easy to further suppress oxidation degradation of the solid electrolyte layer. s There is no particular upper limit, and for example, it may be 0.5 V or less.

[0033] The electrode potential P of the solid electrolyte layer s The sample with the solid electrolyte layer exposed can be immersed in a 1.5 wt % p-toluenesulfonic acid aqueous solution using a silver (Ag / Ag +) is used as a reference electrode for measurement. The sample can be prepared by cutting the capacitor element with a microtome or the like until the solid electrolyte layer is exposed. The electrode potential P1 of the first layer can also be determined according to the electrode potential P s In the case of , the sample in the state where the first layer is exposed is used for measurement. The sample can be prepared by cutting the capacitor element with a slicer or the like as needed until the first layer is exposed.

[0034] The solid electrolyte layer contains a conductive polymer and may further contain at least one of a dopant and an additive as necessary.

[0035] As the conductive polymer, known conductive polymers used in electrolytic capacitors can be used, for example, π-conjugated conductive polymers can be used. As conductive polymers, for example, polymers with polypyrrole, polythiophene, polyaniline, polyfuran, polyacetylene, polyphenylene, polyphenylene vinylene, polybenzone and polythiophene vinylene as basic skeletons can be cited. Among them, polymers with polypyrrole, polythiophene or polyaniline as basic skeletons are preferred. In the above-mentioned polymers, homopolymers, copolymers of two or more monomers and their derivatives (substituents with substituents, etc.) are also included. For example, in polythiophene, poly (3,4-ethylenedioxythiophene) and the like are included.

[0036] The conductive polymer may be used alone or in combination of two or more.

[0037] The weight average molecular weight (Mw) of the conductive polymer is not particularly limited, but is, for example, 1,000 or more and 1,000,000 or less.

[0038] In this specification, the weight average molecular weight (Mw) is a value in terms of polystyrene measured by gel permeation chromatography (GPC). In general, GPC is measured using a polystyrene gel column and water / methanol (volume ratio 8 / 2) as a mobile phase.

[0039] The solid electrolyte layer may further contain a dopant. As the dopant, for example, at least one selected from anions and polyanions may be used.

[0040] Examples of the anion include, but are not particularly limited to, sulfate ions, nitrate ions, phosphate ions, borate ions, organic sulfonate ions, and carboxylate ions. Examples of the dopant that generates sulfonate ions include p-toluenesulfonic acid and naphthalenesulfonic acid.

[0041] As polyanions, for example, high molecular weight polysulfonic acids and high molecular weight polycarboxylic acids can be cited. As high molecular weight polysulfonic acids, polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid and polymethacryl sulfonic acid can be cited. As high molecular weight polycarboxylic acids, polyacrylic acid and polymethacrylic acid can be cited. Polyanions also include polyester sulfonic acid and phenolsulfonic acid novolak resin. However, polyanions are not limited to these.

[0042] The anion and the polyanion may be contained in the solid electrolyte layer in the form of a salt. In the solid electrolyte layer, the anion and the polyanion may form a conductive polymer complex together with the conductive polymer.

[0043] The amount of the dopant contained in the solid electrolyte layer is, for example, 10 to 1000 parts by mass, or 20 to 500 parts by mass or 50 to 200 parts by mass, based on 100 parts by mass of the conductive polymer.

[0044] The solid electrolyte layer may be a single layer or may be composed of multiple layers. When the solid electrolyte layer is composed of multiple layers, the conductive polymer contained in each layer may be the same or different. In addition, the dopant contained in each layer may be the same or different.

[0045] The solid electrolyte layer may further contain known additives and known conductive materials other than the conductive polymer as necessary. Examples of such conductive materials include at least one selected from conductive inorganic materials such as manganese dioxide and TCNQ complex salts.

[0046] In addition, a layer for improving adhesion or the like may be interposed between the dielectric layer and the solid electrolyte layer.

[0047] For example, a solid electrolyte layer is formed by polymerizing the precursor on the dielectric layer using a treatment solution containing a precursor of a conductive polymer. The polymerization can be carried out by at least one of chemical polymerization and electrolytic polymerization. As precursors of conductive polymers, monomers, oligomers or prepolymers can be cited. The solid electrolyte layer can also be formed by attaching a treatment solution (such as a dispersion or solution) containing a conductive polymer to the dielectric layer and then drying it. As a dispersion medium (or solvent), for example, water, an organic solvent, or a mixture thereof can be cited. The treatment solution may also contain other components such as a dopant.

[0048] In the case of using a treatment liquid containing a precursor of a conductive polymer, an oxidant is used to polymerize the precursor. The oxidant may be contained in the treatment liquid in the form of an additive. In addition, the oxidant may be applied to the anode body before or after the treatment liquid is brought into contact with the anode body on which the dielectric layer is formed. Examples of such oxidants include sulfates, sulfonic acids, or salts thereof. The oxidant may be used alone or in combination of two or more. As sulfates, for example, salts of sulfuric acids such as ferric sulfate, sodium persulfate, and sulfuric acids such as persulfate and metals may be cited. As metals that form salts, for example, alkali metals (sodium, potassium, etc.), iron, copper, chromium, zinc, etc. may be cited. Sulfonic acids or their salts have the function of being a dopant in addition to having the function of being an oxidant. As sulfonic acids or their salts, low molecular weight sulfonic acids or their salts, etc., exemplified for dopants may be used.

[0049] The process of forming a solid electrolyte layer by immersion in a treatment solution and polymerization (or drying) can be performed once, or can be repeated multiple times. In each time, the composition and viscosity of the treatment solution can be the same, or at least one condition can be changed.

[0050] For the electrode potential P of the solid electrolyte layer s In the case of forming a solid electrolyte layer using chemical polymerization or a treatment solution containing a conductive polymer, the electrode potential P can be adjusted by selecting the type of conductive polymer and the type of dopant, and adjusting the amount or concentration of the dopant. In the case of forming a solid electrolyte layer using electrolytic polymerization, the electrode potential P can be adjusted by selecting the type of conductive polymer and the type of dopant, adjusting the amount or concentration of the dopant, and adjusting the polymerization potential. s .

[0051] (Cathode extraction layer)

[0052] The cathode lead layer may be provided with at least a first layer that contacts the solid electrolyte layer and covers at least a portion of the solid electrolyte layer, or may be provided with a first layer and a second layer that covers the first layer. As the first layer, for example, a layer containing conductive particles, a metal foil, etc. may be cited. As the conductive particles, for example, at least one selected from conductive carbon and metal powder may be cited. For example, a layer containing conductive carbon as the first layer and a layer containing metal powder or a metal foil as the second layer may be used to form the cathode lead layer. When a metal foil is used as the first layer, the metal foil may be used to form the cathode lead layer.

[0053] The first layer containing conductive carbon can be formed, for example, by immersing an anode body having a dielectric layer formed with a solid electrolyte layer in a dispersion containing conductive carbon, or by applying a paste containing conductive carbon to the surface of the solid electrolyte layer. As conductive carbon, for example, graphites such as artificial graphite and natural graphite, and carbon black can be used. As the dispersion and paste, for example, a material in which conductive carbon is dispersed in an aqueous liquid medium can be used.

[0054] The layer containing metal powder as the second layer can be formed, for example, by laminating a composition containing metal powder on the surface of the first layer. As such a second layer, for example, a metal paste layer formed using a composition containing metal powder such as silver particles and a resin (binder resin) can be used. As the resin, although a thermoplastic resin can also be used, it is preferred to use a thermosetting resin such as an imide resin or an epoxy resin.

[0055] When a metal foil is used as the first layer, the type of metal is not particularly limited, but preferably a valve metal such as aluminum, tantalum, niobium, or an alloy containing a valve metal is used. The surface of the metal foil may be roughened by etching or the like as needed. A chemically generated coating may be provided on the surface of the metal foil, or a coating of a metal (heterogeneous metal) or a non-metallic film different from the metal constituting the metal foil may be provided. Examples of heterogeneous metals and non-metals include metals such as titanium and non-metals such as carbon (conductive carbon, etc.).

[0056] The above-mentioned film of different metal or non-metal (for example, conductive carbon) may be used as the first layer, and the above-mentioned metal foil may be used as the second layer.

[0057] The electrode potential P1 of the first layer can be adjusted by selecting the material and shape of the first layer.

[0058] The thickness of the first layer is, for example, 0.1 μm to 100 μm, may be 0.5 μm to 50 μm, or may be 1 μm to 20 μm.

[0059] The thickness of the second layer is, for example, 0.1 μm to 100 μm, may be 0.5 μm to 50 μm, or may be 1 μm to 20 μm.

[0060] (Isolator)

[0061] When a metal foil is used in the cathode lead-out layer, a separator may be arranged between the metal foil and the anode body. The separator is not particularly limited, and for example, a nonwoven fabric containing fibers of cellulose, polyethylene terephthalate, vinylon, or polyamide (e.g., aliphatic polyamide, aromatic polyamide such as aramid) may be used.

[0062] (other)

[0063] The electrolytic capacitor may be a wound type, a chip type, or a stacked type. For example, the electrolytic capacitor may include a stack of two or more capacitor elements. The configuration of the capacitor element may be selected according to the type of the electrolytic capacitor.

[0064] In the capacitor element, one end of the cathode terminal is electrically connected to the cathode lead layer. For example, a conductive adhesive is applied to the cathode body, and the cathode terminal is bonded to the cathode body via the conductive adhesive. One end of the anode terminal is electrically connected to the anode body. The other end of the anode terminal and the other end of the cathode terminal are respectively led out of the resin outer package. The other end of the anode terminal and the other end of the cathode terminal exposed from the resin outer package are respectively used for welding with a substrate (not shown) on which the electrolytic capacitor should be mounted.

[0065] The capacitor element is sealed using a resin outer package or shell. For example, the material resin of the capacitor element and the outer package (such as uncured thermosetting resin and filler) can be accommodated in a mold, and the capacitor element can be sealed with a resin outer package by transfer molding, compression molding, etc. At this time, the other end side of the anode terminal and the cathode terminal connected to the anode lead drawn from the capacitor element are exposed from the mold respectively. In addition, the electrolytic capacitor can also be formed by accommodating the capacitor element in a bottomed shell in a manner that the other end side of the anode terminal and the cathode terminal is located on the opening side of the bottomed shell, and the opening of the bottomed shell is sealed by a sealant.

[0066] Figure 1 1 is a cross-sectional view schematically showing the structure of an electrolytic capacitor according to an embodiment of the present invention. Figure 1 As shown, the electrolytic capacitor 1 includes a capacitor element 2, a resin outer package 3 that seals the capacitor element 2, and an anode terminal 4 and a cathode terminal 5, each of which is at least partially exposed to the outside of the resin outer package 3. The anode terminal 4 and the cathode terminal 5 can be formed of metal such as copper or a copper alloy. The resin outer package 3 has an approximately rectangular parallelepiped shape, and the electrolytic capacitor 1 also has an approximately rectangular parallelepiped shape.

[0067] The capacitor element 2 includes an anode body 6, a dielectric layer 7 covering the anode body 6, and a cathode body 8 covering the dielectric layer 7. The cathode body 8 includes a solid electrolyte layer 9 covering the dielectric layer 7 and a cathode lead layer 10 covering the solid electrolyte layer 9. In the example shown in the figure, the cathode lead layer 10 includes a carbon layer 11 as a first layer and a metal paste layer 12 as a second layer. The electrode potential P of the solid electrolyte layer 9 is sThe electrode potential P1 of the carbon layer 11 in contact with the solid electrolyte layer 9 is higher than that of the carbon layer 11. As a result, the oxidation degradation of the conductive polymer contained in the solid electrolyte layer 9 is suppressed, thereby suppressing the increase of ESR. In addition, the decrease of electrostatic capacitance is suppressed. Therefore, the reliability of the electrolytic capacitor can be improved.

[0068] The anode body 6 includes a region facing the cathode body 8 and a region not facing the cathode body 8. In the region not facing the cathode body 8, an insulating separation layer 13 is formed in a band-like manner covering the surface of the anode body 6, and the contact between the cathode body 8 and the anode body 6 is restricted. In the region not facing the cathode body 8, the other portion of the anode body 6, excluding the portion adjacent to the cathode body 8, is electrically connected to the anode terminal 4 by welding. The cathode terminal 5 is electrically connected to the cathode body 8 via an adhesive layer 14 formed of a conductive adhesive.

[0069] Example

[0070] Hereinafter, the present invention will be specifically described based on Examples and Comparative Examples; however, the present invention is not limited to the following Examples.

[0071] 《Example 1》

[0072] Follow the steps below to make Figure 1 The electrolytic capacitor 1 (electrolytic capacitor A1) shown in the figure was manufactured and its characteristics were evaluated.

[0073] (1) Preparation of anode body 6

[0074] Anode body 6 was produced by roughening both surfaces of an aluminum foil (thickness: 100 μm) as a base material by etching.

[0075] (2) Formation of dielectric layer 7

[0076] The other end portion of anode body 6 was immersed in a chemical conversion solution, and a DC voltage of 70 V was applied for 20 minutes to form dielectric layer 7 containing aluminum oxide.

[0077] (3) Formation of Solid Electrolyte Layer 9

[0078] An aqueous solution containing a pyrrole monomer and p-toluenesulfonic acid was prepared. The monomer concentration in the aqueous solution was 0.5 mol / L, and the p-toluenesulfonic acid concentration was set to 0.3 mol / L.

[0079] Anode body 6 and counter electrode having dielectric layer 7 formed in (2) above were immersed in the obtained aqueous solution, and electrolytic polymerization was performed at 25° C. and a polymerization voltage of 3 V (polymerization potential relative to a silver reference electrode), thereby forming solid electrolyte layer 9 .

[0080] (4) Formation of cathode body 8

[0081] The anode body 6 having the solid electrolyte layer 9 obtained in (3) above is immersed in a dispersion in which graphite particles are dispersed in water, taken out of the dispersion, and then dried, thereby forming a carbon layer 11 at least on the surface of the solid electrolyte layer 9. Drying is performed at 130 to 180° C. for 10 to 30 minutes.

[0082] Then, a silver paste containing silver particles and a binder resin (epoxy resin) is applied to the surface of the carbon layer 11, and heated at 150 to 200° C. for 10 to 60 minutes to cure the binder resin to form a metal paste layer 12. In this way, a cathode body 8 including the carbon layer 11 and the metal paste layer 12 is formed.

[0083] Capacitor element 2 is manufactured as described above.

[0084] (5) Assembly of electrolytic capacitor 1

[0085] Cathode body 8 of capacitor element 2 obtained in (4) above is bonded to one end of cathode terminal 5 by conductive adhesive layer 14. One end of anode body 6 protruding from capacitor element 2 is bonded to one end of anode terminal 4 by laser welding.

[0086] Then, a resin outer package 3 made of insulating resin is formed around capacitor element 2 by die molding. At this time, the other end of anode terminal 4 and the other end of cathode terminal 5 are drawn out of resin outer package 3 .

[0087] In this manner, the electrolytic capacitor A1 was completed. A total of 20 electrolytic capacitors A1 were produced in the same manner as above.

[0088] (6) Evaluation

[0089] The following evaluations were performed using an electrolytic capacitor or a capacitor element.

[0090] (a) Electrode potential P s and P1

[0091] Using the capacitor element 2, the electrode potential P of the solid electrolyte layer 9 is measured according to the above-mentioned procedure. s And the electrode potential P1 of the carbon layer 11 as the first layer.

[0092] (b) Change rate of ESR and change rate of electrostatic capacitance

[0093] In an environment of 20° C., the initial electrostatic capacitance (μF) of each electrolytic capacitor at a frequency of 120 kHz and the initial ESR (mΩ) at a frequency of 100 kHz were measured using a 4-terminal LCR tester. Then, the average value of 20 electrolytic capacitors was calculated.

[0094] Then, an accelerated test was performed by applying the rated voltage to the electrolytic capacitor for 500 hours at 145°C and 0.4% RH. Thereafter, the electrostatic capacitance and ESR were measured at 20°C using the same procedure as for the initial electrostatic capacitance and ESR, and the average values ​​of 20 electrolytic capacitors were obtained. The ratio (%) of the average value of the electrostatic capacitance after the accelerated test to the average value of the initial electrostatic capacitance was calculated as the rate of change of the electrostatic capacitance (ΔCap). The ratio (%) of the average value of the ESR after the accelerated test to the average value of the initial ESR was calculated as the rate of change of the ESR (ΔESR).

[0095] 《Examples 2 to 3 and Comparative Examples 1 to 3》

[0096] In (3) of Example 1, the concentration of p-toluenesulfonic acid in the aqueous solution was changed, and the polymerization voltage was changed to perform electrolytic polymerization. Except for these, a capacitor element and an electrolytic capacitor were prepared and evaluated in the same manner as in Example 1.

[0097] The evaluation results are shown in Table 1. In Table 1, electrolytic capacitors A1 to A3 are Examples 1 to 3, respectively, and electrolytic capacitors B1 to B3 are Comparative Examples 1 to 3, respectively.

[0098] [Table 1]

[0099]

[0100] Industrial Applicability

[0101] According to the present invention, an electrolytic capacitor having excellent reliability and with suppressed increase in ESR or decrease in electrostatic capacitance can be provided. Such an electrolytic capacitor can be used in various applications requiring high reliability.

[0102] Description of Reference Numerals

[0103] 1 electrolytic capacitor, 2 capacitor element, 3 resin outer package, 4 anode terminal, 4S main surface of anode terminal, 5 cathode terminal, 5S main surface of cathode terminal, 6 anode body, 7 dielectric layer, 8 cathode body, 9 solid electrolyte layer, 10 cathode lead layer, 11 carbon layer, 12 metal paste layer, 13 separation layer, 14 adhesive layer.

Claims

1. An electrolytic capacitor, It has a capacitor element, The capacitor element includes: an anode body, a dielectric layer formed on a surface of the anode body, a solid electrolyte layer covering at least a portion of the dielectric layer, and a first layer in contact with the solid electrolyte layer and covering at least a portion of the solid electrolyte layer. The first layer constitutes at least a part of the cathode extraction layer, The electrode potential P of the solid electrolyte layer s Higher than the electrode potential P1 of the first layer, The electrode potential P of the solid electrolyte layer s is below 0.5V, The solid electrolyte layer includes a conductive polymer.

2. The electrolytic capacitor according to claim 1, wherein: P s The difference from P1 is 0.02V or more.

3. The electrolytic capacitor according to claim 1 or 2, wherein: P s Greater than 0.2V.

4. The electrolytic capacitor according to claim 1 or 2, wherein: The first layer includes conductive carbon.

5. The electrolytic capacitor according to claim 1 or 2, wherein: The cathode extraction layer includes the first layer and a second layer covering at least a portion of the first layer. The second layer contains metal powder. 6 . The electrolytic capacitor according to claim 1 , comprising a laminate of two or more capacitor elements.

7. A capacitor element, The invention comprises: an anode body, a dielectric layer formed on a surface of the anode body, a solid electrolyte layer covering at least a portion of the dielectric layer, and a first layer in contact with the solid electrolyte layer and covering at least a portion of the solid electrolyte layer. The first layer constitutes at least a part of the cathode extraction layer, The electrode potential P of the solid electrolyte layer s Higher than the electrode potential P1 of the first layer, The electrode potential P of the solid electrolyte layer s is below 0.5V, The solid electrolyte layer includes a conductive polymer.

Citation Information

Patent Citations

  • Conductive polymer and solid electrolitic capacitor using the same

    JP2005281410A

  • Solid electrolytic capacitor

    JP2004088073A

  • Solid electrolytic capacitor and manufacturing method thereof

    JP2005286072A